β-Blockers in congestive heart failure - Teh, B.T.; Azman, W.; Thuraisingham, S.; Choy, A.M.; Tan, K.H.; Jesudason, P.; Lang, C.C. (Faculty of Medicine, University of Malaya, 1999)
Activation of the sympathetic nervous system (SNS) and renin-angiotensin system (RAS) plays a pivotal role in the pathophysiology and progression of the disease in chronic heart failure (CHF). Blocking the activation of the RAS with angiotensin converting enzyme inhibitors not only improves symptoms but also prolongs life in symptomatic CHF. Does s similar analogy hold true for the use of B-blockers in CHF? Evidence from a number of small trials and several recent large prospective trials show that B-blocker may improve ventricular function and symptoms in CHF. In a combination of trials investigating the use of carvedilol (an a, and B-blocker) in congestive heart failure a mortality benefit appears to be evident. There are still a number of key question that remain unanswered regarding the tolerability, patient type and stage of CHF in which B-blockers should be advocated. Several large-scale trial are in progress to answer some of these question and also to add further information regarding its efficacy and impact on survivak